Association of Total Serum Calcium Level with Obesity Markers (Body Mass Index and Waist Circumference) among Healthy Young Saudis - Abdelmarouf H. Mohieldein, Sami Ali Al-Moshawah, Mahmoud I. Elhabiby, Ayman Abu Mustafa, (Pakistan Journal of Medical & Health Sciences, 2023)
Background & Objective: The pathophysiology of obesity and comorbid diseases may be associated with the levels of intracellular and extracellular calcium. This study aimed to investigate the association between overweight/obesity measures and the total serum calcium level in young Saudis. Methods: This was a cross-sectional observational study that involved 121 healthy young Saudi participants of both genders. Venipuncture was performed to obtain blood samples of 4 ml. Serum specimens were extracted and aliquoted into Eppendorf tubes, then preserved at a temperature of -20°C until the time of analysis. Anthropometric Measures (BMI and WC) were measured. SPSS software was used for statistical analysis. The measurement of total serum calcium was conducted through the utilization of a Human Diagnostics kit (Wiesbaden, Germany) on a hospitex Diagnostics Eos-bravo Autoanalyzer. The statistical analysis was conducted using the SPSS software. Results: The sample population consisted of 87.6% males, 27.3% smokers, 57% students, and 66.9% individuals with a university degree or higher. Nearly 50% of participants were 15–23 years old. Obese subjects had considerably lower total serum calcium than normal weight subjects. BMI and WC inversely correlated with calcium levels. Conclusion: The present study confirms the inverse relationship between total serum calcium level and obesity in the Saudi healthy population. Calcium supplementation could lower obesity-related chronic disease mortality and morbidity and hence reduce healthcare expenses and increases healthy life years. Keywords: calcium; obesity; overweight; waist circumference; body mass index; Saudi Arabia.